Web-based E-Commerce Application for MSME in Manado - Gabriell Cristiano Agung Taroreh; Benny Pinontoan; Edwin Tenda; Christian Soewoeh; Wisard Kalengkongan; Dodisutarma Lapihu (PT. Tech Cart Press, 2026)
Digital transformation has opened new opportunities for Micro, Small, and Medium Enterprises (MSMEs) in Manado City to increase market reach and strengthen business competitiveness through online transactions. However, many local MSMEs still have limited access to independent digital platforms, while existing e-commerce systems do not always provide the flexibility needed to handle both physical products and service-based offerings in a localized context. This study aims to design and implement a web-based MSME marketplace for Manado City using the Waterfall software development method. The system was developed with a decoupled architecture consisting of Next.js as the frontend framework, Strapi Headless CMS for backend management, and PostgreSQL as the database. The main features include seller store registration, product and service catalog management, dynamic product variants, map-based location pinning, Live Commerce, Midtrans payment gateway integration, order tracking, and accessibility support. System evaluation was conducted using Black-Box Testing and User Acceptance Testing (UAT) with a five-point Likert scale involving buyer and seller respondents. The Black-Box Testing results show that all tested features functioned as expected. The UAT results produced an average acceptance rate of 89.88% from buyers and 91.38% from sellers. These results indicate that the proposed marketplace is functional, practical, and well accepted by users, making it a suitable digitalization solution for supporting MSMEs in Manado City.